The Metrics of Teacher Effectiveness and Teacher Quality Research: Sidelining the Issues that Really Count, 1st edition - Andrew, Skourdoumbis (Routledge, 2020)
Most developed nations measure the performance of teachers in audit evaluations of school productivity. Accountability metrics such as "teacher effectiveness" and "teacher quality" dominate evaluations of student outcomes and shape education policy.